Single step, phase controlled, large scale synthesis of ferrimagnetic iron oxide polymorph nanoparticles by thermal plasma route and their rheological properties - Raut, Suyog A.; Mutadak, Pallavi R.; Kumar, Shiv; Kanhe, Nilesh S.; Huprikar, Sameer; Pol, Harshawardhan V.; Phase, Deodatta M.; Bhoraskar, Sudha V.; Mathe, Vikas L. (Journal of Magnetism and Magnetic Materials, 2018)
In this paper we report single step large scale synthesis of highly crystalline iron oxide nanoparticles viz. magnetite (Fe3O4) and maghemite (gamma-Fe2O3) via gas phase condensation process, where micron sized iron metal powder was used as a precursor. Selective phases of iron oxide were obtained by variation of gas flow rate of oxygen and hence partial pressure of oxygen inside the plasma reactor. Most of the particles were found to possesses average crystallite size of about 20-30 nm. The DC magnetization curves recorded indicate almost super-paramagnetic nature of the iron oxide magnetic nanoparticles. Further, iron oxide nanoparticles were analyzed using Raman spectroscopy, X-ray photoelectron spectroscopy and Mossbauer spectroscopy. In order to explore the feasibility of these nanoparticles for magnetic damper application, rheological studies have been carried out and compared with commercially available Carbonyl Iron (CI) particles. The nanoparticles obtained by thermal plasma route show improved dispersion which is useful for rheological applications. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Iron oxide; magnetic properties; Nano-crystalline materials; Rheological properties; Thermal plasma

Microstructure and yielding of capillary force induced gel - Huprikar, Sameer; Usgaonkar, Saurabh; Lele, Ashish K.; Orpe, Ashish V. (Rheologica Acta, 2020)
We have investigated the rheology and structure of a gel formed from a mixture of non-Brownian particles and two immiscible liquids. The suspension of particles in a liquid undergoes gelation upon the addition of a small content of second, wetting liquid which forms liquid bridges between particles leading to a sample spanning network. The rheology of this gel primarily exhibits a yield stress at low shear rates followed by a linear variation of shear stress at high shear rates. The apparent yield stress extracted from the flow curves increases rapidly with volume fraction of the second liquid before saturation, while it exhibits a monotonic increase with increasing particle concentration. Rescaling of the yield stress curves using suitable shift factors results in an empirical expression for the yield stress showing squared dependence on liquid fraction and a rapid increase with particle fraction above a certain value, both combined in a highly non-linear manner. The microstructural variations with changing secondary liquid content and particle fractions are captured using three-dimensional X-ray tomography technique. The microstructure is observed to show increased local compactness with increased liquid content and increased spatial homogeneity with increased particle fractions. The images from X-ray tomography are analysed to obtain the distributions of particle-particle bonds (coordination number) in the system which serve to explain the observed yield stress behaviour in a qualitative manner.
Keywords: Capillary force; Flow curve; gel; Microstructure; Rheology; Yield stress